2008
DOI: 10.2220/biomedres.29.195
|View full text |Cite
|
Sign up to set email alerts
|

Changes of HCN gene expression and If currents in Nkx2.5-positive cardiomyocytes derived from murine embryonic stem cells during differentiation

Abstract: Changes in the expression of hyperpolarization-activated cyclic nucleotide (HCN)-gated channels and I f currents during the differentiation of embryonic stem cells into cardiac cells remain unknown. We examined changes of HCN genes in expression and function during the differentiation of Nkx2.5-positive cardiac precursor cells derived from mouse ES cells using cell sorting, RT-PCR, immunofluorescence and whole cell patch-clamp techniques. Cs + -induced inhibition of automaticity and transcription of HCN genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Both HCN1 and HCN2 are predominantly N-glycosylated in brain tissue (31,39,58), but whether these channels are N-glycosylated in cardiac tissue is unknown. HCN1 and HCN2 are expressed in conduction tissue of the adult heart (28 -30, 43) and are found in various regions of embryonic and neonatal hearts (45,56) and in cardiac embryonic stem cells (36,40,41,55). Studies from our lab (36,53) and others (16,24,26,45,56) have shown that HCN2 contributes to the generation and modulation of heart rate in the embryonic stage, and knockout of HCN2 leads to significant reductions in hyperpolarizationactivated current (I h ) amplitudes recorded from individual embryonic cardiac myocytes (26).…”
Section: Hcn2 Channels Undergo N-glycosylation In Native Cardiacmentioning
confidence: 99%
“…Both HCN1 and HCN2 are predominantly N-glycosylated in brain tissue (31,39,58), but whether these channels are N-glycosylated in cardiac tissue is unknown. HCN1 and HCN2 are expressed in conduction tissue of the adult heart (28 -30, 43) and are found in various regions of embryonic and neonatal hearts (45,56) and in cardiac embryonic stem cells (36,40,41,55). Studies from our lab (36,53) and others (16,24,26,45,56) have shown that HCN2 contributes to the generation and modulation of heart rate in the embryonic stage, and knockout of HCN2 leads to significant reductions in hyperpolarizationactivated current (I h ) amplitudes recorded from individual embryonic cardiac myocytes (26).…”
Section: Hcn2 Channels Undergo N-glycosylation In Native Cardiacmentioning
confidence: 99%
“…Nkx2.5, which are some of the first cardiomyocyte marker genes to be upregulated upon initiation of cardiomyocyte differentiation (Boheler et al, 2002). Nkx2.5 is the major homeobox transcription factor that regulates expression of genes in the cardiomyocyte lineage and a marker of cardiac progenitor cells (Yano et al, 2008). Nkx2.5 expression is repressed by the homeodomain transcription factor encoded by the Shox2 homeobox gene (Espinoza-Lewis et al, 2009), and as shown in Figures 2 and 3 and Table 1, one of the major effects of TCDD treatment was a 50-fold induction of Shox2, suggesting the possibility that through inhibition of Nkx2.5 expression and of Nkx2.5-regulated cardiovascular markers, TCDD treatment might block attainment of the cardiomyocyte phenotype.…”
Section: Tcdd Inhibits Cardiomyocyte Differentiationmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) are a feasible starting material, as they are pluripotent and can be differentiated to any cell lineage. Several ESC reporter lines have been engineered and used to isolate CCS cells, including (1) HCN4p-EGFP + cells that express transcripts for CCS markers Hcn4 , Cav3.2 , and Cx40 and display a hyperpolarization-activated depolarizing current (termed the funny current; Morikawa et al., 2010); (2) an ESC reporter line containing a Mink:lacz transgene and a reporter regulated by a chicken Gata6 ( cGata6 ) enhancer; the double-positive cells display pacemaker-like morphology and show pacemaking action potential waveform as well as a funny current (White and Claycomb, 2005); (3) a Shox2 promoter with a Cx30.2 enhancer to generate ESC-derived SHOX2 + and Cx30.2 + cardiomyocytes that express additional CCS markers ( Hcn4 , Cx45 , Cx30.2 , Tbx2 , and Tbx3 ) and exhibit pacemaker-nodal phenotype (Hashem and Claycomb, 2013); (4) ESC-derived Nkx2.5:GFP + cells expressing Hcn1 and Hcn4 that display the funny current (Yano et al., 2008); and (5) an ESC reporter line derived from Contactin2:EGFP BAC transgenic mice ( Cntn2:egfp ) was recently used to isolate rare cells that display transcriptional signatures and functional properties comparable to endogenous cardiac Purkinje cells (PCs) (Maass et al., 2015). Finally, CD166 has been identified as a CCS cell-surface marker (Scavone et al., 2013), although it is not specific to CCS constituents.…”
Section: Introductionmentioning
confidence: 99%